Investigating neurodevelopmental defects in MELAS syndrome using neural organoids derived from induced pluripotent stem cells - Khong, Zi Jian (2018)
Mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) syndrome is characterised by many neurological symptoms such as dementia and epilepsy. One of the most prevalent mutation in MELAS is the m.A3243G transition within the MT-TL1 gene, that encodes for mitochondrial tRNALeu(UUR). This mutation has been shown to affect oxidative phosphorylation (OXPHOS) by reducing the protein synthesis of mitochondrial respiratory chain complexes. Hence, we hypothesize that MELAS iPSCs will exhibit neurodevelopmental defects upon differentiation into cortical neurons (CNs), as neurons fuel most of its metabolic demands through OXPHOS. Here, we uncover neurodevelopmental defects in MELAS by differentiating MELAS iPSCs into CNs using three different methods. Using our 2D differentiation protocol, we found that MELAS iPSCs differentiated poorly towards NPCs and observed an abnormal accumulation of lipids within NPCs, which has not been reported previously. Through the 3D organoid protocol, we determined that MELAS iPSCs showed delayed differentiation into CNs, generating large pools of NPCs arranged in large rosette-like structures within the organoids. Finally, we showed that MELAS CNs have significantly smaller soma size through rapid NGN2 induction. Overall, our results showed that MELAS iPSC exhibited neurodevelopmental defects and identified several key cellular phenotypes that could be used for eventual drug screening.